Improving the accuracy of revised cardiac risk index with HbA1C: Hemoglobin ratio (HH ratio) – A retrospective cohort study - Ke, Yuhe; Shannon, Nicholas Brian; Abdullah, Hairil Rizal (Frontiers in Medicine, 2023)
Background The current Lee’s Revised cardiac risk index (RCRI) was created in 1999. Validation studies have found RCRI to be only moderately discriminant. The “Diabetes Mellitus on insulin” component of the score does not accurately reflect the severity of the disease. A previously studied HbA1C:Hemoglobin ratio shows an improved association with outcomes than individual components alone. Study design A retrospective cohort study was performed in diabetic patients undergoing non-cardiac surgery. Ethics approval was obtained. The study compares the predictive value of RCRI and substitution of the “DM on insulin” component with HH ratio for 30- and 90-day mortality, and postoperative acute myocardial injury(AMI) and acute kidney injury(AKI). Results A total of 20,099 adult patients were included in the final analysis. The incidence of 30- and 90-day mortality was at 4.2% and 6.5% respectively. Substitution of HH ratio in RCRI resulted in 687 more patients being in the moderate to high-risk category. The substituted HH-RCRI score had better prediction for 30-day (AUC 0.66 vs 0.69, p<0.001) and 90-day mortality (AUC 0.67 vs 0.70, p<0.001), and postoperative AMI (AUC 0.69 vs 0.71, p<0.001) and AKI (AUC 0.57 vs 0.62, p<0.001). Conclusions Although currently not an universal practice, substitution of “DM on insulin” with HbA1C:Hemoglobin ratio in RCRI score improves the accuracy of the RCRI risk prediction model in diabetic patients going for non-cardiac surgery.